Aplikasi Pembelajaran Interaktif “Perang Padri” Menggunakan X-Box Kinect Untuk Meningkatkan Minat Siswa Dalam Mempelajari Sejarah Bangsa Indonesia - Azka Ramadhona; Meilany Dewi; Silvana Rasio Henim (TEKNIK, 2017)
A well recognition and understanding national history plays an important role in shaping the character of nation, especially Padri War history which tells about a dispute between two clans but then allied to defend against invaders. History’s subject in school which is taught by telling story and reading books makes student not interested in studying history. In this case, we need a different approach to makes student in fifth grade more interested to learn it. One of alternative learning media that can be applied to fifth graders is the application of Padri War. In this application, Padri War is described in 3D animation video and there are many of trivial questions in it to test user ability. The result of the application testing conducted to five teacher respondents concludes this interactive application could be the best alternative learning method for fifth grade elementary school student today. The conclusion reflects on the assessment indicators of 80% material aspect, 72.5 % general aspect, 78,9% quality display, presentation of the material to 75%, and 84% of user interaction. On the student respondents, the visual design aspect in the Padri War learning is worth 79.3%. Overall, presentation study material in the form of 3D animation video would certainly increase the interest of elementary students in learning history.